2015
DOI: 10.1093/mnras/stv1961
|View full text |Cite
|
Sign up to set email alerts
|

Star-forming regions at the periphery of the supershell surrounding the Cyg OB1 association – I. The star cluster vdB 130 and its ambient gas and dust medium

Abstract: Stellar population and the interstellar gas-dust medium in the vicinity of the open star cluster vdB 130 are analysed using optical observations taken with the 6-m telescope of the SAO RAS and the 125-cm telescope of the SAI MSU along with the data of Spitzer and Herschel. Based on proper motions and BV and JHKs 2MASS photometric data, we select additional 36 stars as probable cluster members. Some stars in vdB 130 are classified as B stars. Our estimates of minimum colour excess, apparent distance modulus and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…For that reason, we didn't exclude this object from the list of clusters inside the Cygnus OB1 association. The cluster vdBergh 130 is located at the upper distance limit (1.8 kpc), according to Sitnik et al (2015), together with IC 4996, which is also located close to the farther border of the association.…”
Section: Radial Velocity Measurementsmentioning
confidence: 98%
See 2 more Smart Citations
“…For that reason, we didn't exclude this object from the list of clusters inside the Cygnus OB1 association. The cluster vdBergh 130 is located at the upper distance limit (1.8 kpc), according to Sitnik et al (2015), together with IC 4996, which is also located close to the farther border of the association.…”
Section: Radial Velocity Measurementsmentioning
confidence: 98%
“…In this field of view, 13 stellar clusters are catalogued. The summarized information about these objects is in Table 2, where the coordinates, the parent OB association, the central RV values given by WEBDA and SIMBAD, respectively, and other cluster parameters like distance, reddening and age taken from four different studies (Loktin, Gerasimenko & Malisheva 2001;Dias et al 2002;Kharchenko et al 2005;Sitnik et al 2015) are shown. The cluster positions are drawn in Fig.…”
Section: Radial Velocity Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of them, like Cygnus OB1, OB8 and OB9 have been proposed to be part of a single structure (Mel'Nik & Efremov 1995), and it has been suggested that the differences between Cygnus OB2 and OB9 are due to the progression of star formation from lower to higher galactic longitudes rather than to distinct, independent episodes of star formation (Comerón et al 2008;Comerón & Pasquali 2012). Despite large uncertainties and conflicting results, sometimes yielding discrepant distances by factors up to 2 for the same cluster (Straižys et al 2014), most studies yield values in the 1.3-1.8 kpc range for the associations in the area under consideration (e.g., Garmany & Stencel 1992;Hanson 2003;Kharchenko et al 2005;Comerón & Pasquali 2012;Straižys et al 2014Straižys et al , 2019Sitnik et al 2015). Distances to structures in the interestellar medium have been established through evidence of physical links with OB associations, as illustrated by Schneider et al (2007).…”
Section: The Distance To the Cygnus Regionmentioning
confidence: 99%
“…In Sitnik et al (2015) (hereinafter referred to as Paper I) and Tatarnikova et al (2016) we have already partially studied the regions of ongoing star formation located in the supershell and related to the globule family (Arkhipova et al 2013) and the cometary molecular cloud, or pillar . A young (5 − 10 Myr) star cluster vdB 130 (Racine 1968) is observed in the direction of the head of the CO cloud (see square on Fig.…”
Section: Introductionmentioning
confidence: 99%